The Market Impact and Timing of Open Market Share Repurchases in Norway - Johannes A. Skjeltorp (Norges Bank, 2004)
This paper examines a detailed dataset on open market repurchase announcements and actual repurchases conducted by Norwegian firms during the period 1998-2001. Firms that announce a repurchase plan experience a positive excess return around the announcement date. However, these firms also experience an abnormal performance after the announcement, suggesting that the market underreacts to the positive signal conveyed through the announcement. When examining the sample of actual repurchases, we find that there is a positive price impact around the execution dates, indicating that the market puts a positive value on the information conveyed through the actual repurchases. In the long run, only announcing firms that do not repurchase experience a significant positive abnormal performance, while a portfolio tracking the repurchasing firms perform according to expectations. In addition, announcing firms that do not repurchase are less liquid than repurchasing firms. One suggested explanation for the finding is that firms by executing repurchases mitigate the undervaluation by confirming their initial signal through actual transactions such that these firms perform as expected in the long run. Due to the lower liquidity of non-repurchasing firms, they are likely to be constrained from exploiting mispricing and unable to signal undervaluation to the market. If this is the case, the price remains too low, and information surprises in later periods contribute to the long term abnormal return drift for these companies.
hdl:11250/2498545
Keywords: G14; G32; 330; open market share repurchases; asymmetric information